An Empirical Exploration of Exchange Rate Target-Zones - Mathieson, Donald (IMF Working Papers; Working Paper ;, 1991)
In the context of a flexible-price monetary exchange rate model and the assumption of uncovered interest parity, we obtain a measure of the fundamental determinant of exchange rates. Daily data for the European Monetary System are used to explore the importance of nonlinearities in the relationship between the exchange rates and fundamentals. Many implications of existing 'target-zone' exchange rate models are tested; little support is found for existing nonlinear models of limited exchange rate flexibility.